Thermogravimetric analysis of teeth for forensic purposes - Lozano Peral, Diego; Arango Díaz, Ana; Martín-de-las-Heras, Stella; Rubio-Lamia, Leticia Olga (Springer Link, 2020)
The objectives of this study were to characterize the thermal decomposition of human teeth and to evaluate the decomposition of organic matter, including DNA, at different temperatures. Eight teeth were chemically characterized by thermogravimetric analysis coupled with mass spectroscopy, conducting evolved gas analyses at temperatures up to 1000 °C and 60-min isothermal assays at 50, 100, 150, 200, 250, 300, 350, and 400 °C. Mass losses (total of 25.2%) were associated with: loss of free water at temperatures between 44 and 210 °C, combustion of organic matter between 211 and 603 °C, and decomposition of inorganic matter between 604 and 940 °C. The first organic fragment detected was sulfur dioxide (linked to protein decomposition), which showed a major peak at around 270 °C, while volatile DNA residues were recorded between 330 and 347 °C. Isothermal assay results showed that carbon dioxide molecules (associated with organic matrix decomposition) were already present between 150 and 200 °C, indicating the start of organic matter degradation and a potential negative effect on DNA integrity at this temperature range. The most severe decomposition of organic matter started between 200 and 250 °C. These data contribute to knowledge on the decomposition of organic matter, particularly DNA, under thermal conditions encountered in forensic scenarios requiring the genetic identification of fire-damaged humans.
Keywords: Antropología dental; Teeth; DNA; Identification; Thermogravimetric analysis; Mass spectroscopy